Understanding Academic Persistence through the Theory of Planned Behavior: Normative Factors under Investigation. (August 2018) - Roland, Nathalie; Frenay, Mariane; Boudrenghien, Gentiane
High drop-out rates among first-year university students have led many researchers to attempt to gain a better understanding of academic persistence. However, despite this extensive literature, only a few studies have taken normative factors into account. These normative factors may be an essential factor of influence for persistence as it is already the case for other behaviors. We therefore decided to study whether including injunctive and descriptive norms in the investigation might improve the understanding of persistence. To this end, we focused on the theory of planned behaviour which considers for background, motivational, and normative factors. Seven hundred and twenty-seven first-year college students were asked to complete a self-report questionnaire. A structural equation modeling technique revealed that the model including injunctive norms fits better with the data than the model without norms. However, this was not the case with descriptive norms. These results are examined in the Discussion section. Finally, directions for future research and practical implications are suggested.